1987
DOI: 10.1021/ef00002a005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mobility during pyrolysis of Australian bituminous coals

Abstract: tetralins) as well as decomposition of labile functional groups (e.g., carboxylic moieties) takes place around 300 °C during the early stages of decomposition of the Hiawatha coal. The main degradation step Occurs between 500 and 600 °C when the "bulk" components of the coal start to decompose. A third stage consists of char-forming reactions characterized by the evolution of small, stable molecules and aromatic hydrocarbon moieties.Weathering has an effect on all degradation steps. The alkylnaphthalenés and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Iglesias et al (2002) suggested that hydrogen enrichment in these coals is responsible for their anomalous properties. As Sakurovs et al (1987) reported when studying Australian bituminous coals, the hydrogen content in coal has a strong influence on the maximum extent of mobile material attained during the pyrolysis. Therefore, it is suggested that the abnormal thermoplastic behaviors in these coals are related to the high hydrogen content.…”
Section: Thermoplastic Properties Of Coalsmentioning
confidence: 75%
“…Iglesias et al (2002) suggested that hydrogen enrichment in these coals is responsible for their anomalous properties. As Sakurovs et al (1987) reported when studying Australian bituminous coals, the hydrogen content in coal has a strong influence on the maximum extent of mobile material attained during the pyrolysis. Therefore, it is suggested that the abnormal thermoplastic behaviors in these coals are related to the high hydrogen content.…”
Section: Thermoplastic Properties Of Coalsmentioning
confidence: 75%
“…Of the in-situ analytical techniques available, high-temperature in-situ 1 H NMR has proved to be the most successful for investigating the molecular motions of coals during carbonization. There are usually two contributions to the free induction decays (FIDs) of coals arising from mobile (faster relaxing) and rigid (slower relaxing) components, which display Lorentzian and Gaussian decays, respectively gives rise to a substantial inert component that does not soften, and this produces the broad Gaussian peak in the 1 H NMR spectra with a much narrower Lorentzian peak from the mobile material superimposed. , Indeed, the peak width or spin−spin relaxation time ( T 2 ) of the fluid phase is highly responsive to changes in mobility …”
Section: Introductionmentioning
confidence: 99%
“…In most of the studies with PMRTA, the overall concentrations of fluid and inert material over the thermoplastic range have not often being reported, possibly due to a combination of convenience for handling large data sets and the likelihood of truncating broad Gaussian signals at high temperatures where sensitivity is lowest. This has been achieved here using a high-temperature Doty NMR probe operating at a frequency of 100 MHz.…”
Section: Introductionmentioning
confidence: 99%
“…However, the proportions of fluid and rigid material during the thermoplastic range have not often been reported in PMRTA studies. 22 Three of the authors have achieved this goal by using a high-temperature Doty NMR probe to characterize coal thermoplasticity both in terms of the proportions of rigid (Gaussian) and fluid (Lorentzian) components and the of mobility (T 2 ) of the fluid phase. 23 It was possible to rationalize a number of carbonization phenomena, including particle size, mild oxidation and heating regime effects in terms of both the mobility or T 2 , and amount of the fluid phase for temperatures up to 600 °C.…”
Section: Introductionmentioning
confidence: 99%
“…They have mainly gauged changes in fluidity by using the empirical parameter M 2T16 , which corresponds to the frequency of a truncated spectrum at 16 kHz. However, the proportions of fluid and rigid material during the thermoplastic range have not often been reported in PMRTA studies . Three of the authors have achieved this goal by using a high-temperature Doty NMR probe to characterize coal thermoplasticity both in terms of the proportions of rigid (Gaussian) and fluid (Lorentzian) components and the of mobility ( T 2 ) of the fluid phase .…”
Section: Introductionmentioning
confidence: 99%